Kecenderungan Tekstual Pada Tafsir Ayat-Ayat Gender: Telaah Penafsiran Wahbah az-Zuhaili Dalam Kitab Tafsir al-Munir - Zulfikar, Eko; Abidin, Ahmad Zainal (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
This paper discusses several interpretations of the verse about gender in the Tafsir al-Munir by Wahbah az-Zuhaili.The themes discussed include; the origin of women's creation, the 1:2 inheritance formula for women, and women?s leadership in the household. Using the method of constructivism and analysis of intertextuality data, this paper concludes that the interpretation put forward by az-Zuhaili related to these three themes has a different understanding from the contemporary commentators. In the first interpretation (the origin of the creation of women), az-Zuhaili seems to carry gender equality. While the other two things (the inheritance formula 1:2 and household leadership), the interpretation seems to contain subordination (women are lower than men) and marginalization (impoverishment) for women. These three interpretive themes about gender verses show that az-Zuhaili interpreted them in a textual way ? not contextual. Though he lives in contemporary times which incidentally the majority of commentators interpret the Qur'anic verses in a contextual way